Selected factors related to behavior control by executive function in Thai preschool children with epilepsy - Pawanrat Panjatharakul; Rutja Phuphaibul; Suporn Wongvatunyu; Anannit Visudtibhan (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This descriptive correlational study describes behavior control by executive function (EF) and explores the relationship among age at seizure onset, duration of epilepsy, seizure frequency, number of antiepileptic drugs (AEDs), family income, the caregiver's education, home environment and behavior control by EF in preschool children with epilepsy. Design/methodology/approach - The purposive sample was 69 caregivers of preschool children with epilepsy. Data were collected in two medical centers in Bangkok from June 2019 to February 2020. The research instruments constituted: (1) a sociodemographic and medical information form for children with epilepsy and the caregiver; (2) early childhood-home observation for the measurement of the environment (EC-HOME) inventory and (3) the behavior rating inventory of executive function-preschool version® (BRIEF-P). The data were analyzed using Pearson's product-moment correlation and Spearman's Rho correlation. Findings - Most of the participants had quite high scores on home environment (mean = 44.35) and mildly elevated levels of EF deficit (mean = 61.04). The duration of epilepsy and the number of AEDs were positively correlated with behavior control by EF. Family income was negatively associated with behavior control by EF. However, age at seizure onset, seizure frequency, the caregiver's education and home environment had no association with behavior control by EF. Originality/value - Preschool children with epilepsy have poor behavioral control by EF. Consequently, healthcare providers should promote interventions in children to control seizures and to decrease the factors that impact the development of EF.